In search of lost time: An ensemble of policies to restore fiscal progressivity and address the climate challenge - Demetrio Guzzardi; Elisa Palagi; Tommaso Faccio; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
The European Union needs to raise significant resources to finance a just green transition. At the same time, there is a widespread fiscal regressivity in many EU countries. Indeed, recent empirical evidence shows that the tax systems of many EU members are characterized by low degrees of progressivity, with high-income groups paying lower effective tax rates vis-a-vis middle- and low-income classes. In order to jointly tackle such issues, we propose an ensemble of tax policies at the EU level grounded on the recent proposals advanced in the literature. This fiscal reform includes a wealth tax targeting the top 1% of wealth holders, a tax on unrealized capital gains, and an increase of the minimum corporate tax. Our first estimates suggest that these measures can generate substantial yearly revenues in the order of 1.9%-2.9% of EU GDP. Such resources can contribute to the funding of the additional climate mitigation and adaptation policies required to tackle the climate emergency, while reducing inequality, thus contributing to put EU economies on sustainable and inclusive growth pathways.
Keywords: D31; H2; H5; 330; Taxation; Inequality; Wealth tax; Capital gains tax; Corporate tax; Climate change